Right Posterior Segmental Hepatic Duct: Role of Intraoperative Cholangiogram to Prevent Extrahepatic Biliary Duct Injuries - SM, Ikhwan; O, Hairol; J, Razman; Z, Zamri; C, Affirul (IIUM Medical Journal Malaysia, 2015)
Extrahepatic bile ducts constitute a significant anatomic site for surgeons when performing hepatobiliary operations from minor procedure such as cholecystectomy to major operation such as hepatectomy. The challenges for surgeon in performing such cases increase when congenital variance of biliary tree occurs which may lead to unintentional bile duct injuries. We reported a case of a lady who presented with obstructive jaundice secondary to huge distal common bile duct stone. The presence of right posterior segmental hepatic duct, which rarely occurs, was discovered during intraoperative cholangiogram before common bile duct exploration. The operation was successful without incidence of biliary duct injury.